Between superimposition and local initiatives: Making sense of ‘implementation gaps’ as a governance problem of antimicrobial resistance - Maren Jeleff; Christian Haddad; Ruth Kutalek (SSM: Qualitative Research in Health, 2023)
Mitigating antimicrobial resistance (AMR) is a global imperative. Part of this effort is the translation of the Global Action Plan into National Action Plans on AMR (NAPs-AMR). However, effective implementation of these plans remains a governance challenge worldwide.This study aims to explore the apparent implementation gap as a governance problem in Austria by examining the situated perspectives of key experts and stakeholders involved in AMR-related policy and practice. Data were collected through semi-structured qualitative interviews, a focus group discussion, and participation in various symposia on AMR. Data analysis revealed key themes the experts have identified as decisive factors shaping AMR governance, which they perceive as insufficient. These include: the absence of a binding legal framework, incomplete and lacking AMR data, low risk perception, lack of funding mechanisms, and absence of an incentive system for people working in AMR stewardship.The interpretation of these findings suggests policy fragmentation, scattered responsibilities, agenda conformity and a lack of symbolic and material recognition as central features that impede a comprehensive, sustainable and effective AMR-related governance. These insights highlight a tension between local efforts to precipitate longer-term adaptations to prepare for and mitigate effectively AMR on the one hand, and the current approach of ‘superimposing’ reforms onto existing institutional structures. Effective and sustainable measures to address AMR require a fundamental restructuring process of institutional responsibilities, professional routines, and social practices to prioritize AMR stewardship as a guiding principle.